Landslide susceptibility mapping: a technical note - Sorooshian, Sharyar; Li, Wenping; Ismail, Md Yusof (E-Journal of Geotechnical Engineering, 2015)
The ‘Electronic journal of geotechnical engineering’ has recently published a high impact research in the field of landslide susceptibility mapping. This article has a great scientific value with considerable contribution to the knowledge. The aim of current article, as a technical note, is to review some parts of the mentioned landslide susceptibility mapping study with additional discussion on the used methodology. This article tries to suggest alternative methodologies to support/validate the found ‘landslide susceptibility index’ formula from the mentioned published research. Author of this paper adds to the review of the mentioned article from a different angle, alternative calculation and formulation methods. KEYWORDS: Alternative method; AHP, Landslide susceptibility mapping.